Analisis Implementasi Good Amil Governance berdasarkan Zakat Core Principle di Lembaga Amil Zakat: Studi pada LAZ Nurul Hayat, Surakarta - Hartomi Maulana; Muhammad Zuhri (Al Tijarah, 2020)
The development of zakah in Indonesia increased significantly when Law no. 38/1999 was introduced by the government. However, problems arise with the growth of the Amil Zakat Institution (LAZ) due to a lack of understanding of zakat regulations, for example the misuse of zakat funds, zakat distribution in the form of loan, and using zakat assets for investment. Good Corporate Governance (GCG) and Zakat Core Principle (ZCP) are systems that aim to realize good management of zakat institutions that lead to manage professionally and transparently. The purpose of this study is to analyze good Amil Governance and also to assess Amil Governance based on ZCP in LAZ Nurul Hayat Surakarta. This study uses a qualitative method with interview, observation, and documentation as data collection techniques. Thematic analysis is used as an analysis technique. The results of the study concluded that LAZ Nurul Hayat Surakarta has carried out a fairly good governance of amil and the implementation of the zakat core principle has been carried out well regarding amil management in this institution.